Counting clowns: bedtime books - Watson, Brown (Brown Watson England, 1992)
"Counting Clowns" is a playful and engaging children's book that introduces young readers to numbers through a fun circus theme. Each page features colorful illustrations of clowns engaging in various antics, encouraging kids to count them as they appear. The story combines learning with entertainment, making it a delightful way to practice counting and foster a love for numbers in an imaginative setting.